ナンキョク ショウワキチ ニ オケル フーリエ ヘンカン セキガイ ブンコウキ (FTIR) ヲ モチイタ キョクセイソウケン クモ (PSC) ノ トクセイ ヒョウカ - 中島, 英彰; ナカジマ, ヒデアキ; 佐伯, 浩介; サエキ, コウスケ; 矢吹, 正教; ヤブキ, マサノリ; 塩原, 匡貴; シオバラ, マサタカ; Nakajima, Hideaki; Saeki, Kosuke; Yabuki, Masanori; Shiobara, Masataka (2010)
P(論文) 極成層圏雲(PSC)は,その表面上での不均一反応により,塩素や臭素といったラジカルを閉じ込めているリザーバー分子から塩素・臭素を活性化させ,大規模なオゾン破壊の引き金を引くため,その特性評価の解明が望まれている.しかし,これまでは直接観測の難しさなどから,なかなかその特徴に関しては明らかにされてこなかった.我々は,第48次日本南極地域観測隊による越冬観測期間中に,低分解能フーリエ変換赤外分光器(FTIR)を用いた地上からのPSCの特性評価観測を南極昭和基地において世界で初めて立ち上げた.昭和基地では2007年7-8月にかけて,数多くのPSCイベントがMPLデータから確認された.これらの日のFTIR赤外放射スペクトルから,Ice(Type-II),NADもしくはβ-NAT(Type-Ia),及びSTS(Type-Ib)PSCの存在が示唆された. Polar stratospheric clouds (PSCs) play an important role in ozone destruction via the occurrence of heterogeneous reactions on their surface that convert reservoir species of active chlorine and bromine (e.g., HCl, ClONO_2, HBr, or BrONO_2) into active Cl_2 or Br_2. However, a lack of direct measurements means that uncertainty remains regarding the characteristics, types, mixtures, and nature of PSCs. To address this problem, we conducted, for the first time, ground-based measurements of the features of PSCs using a low-resolution Fourier-transform infrared (FTIR) spectrometer at Syowa Station, Antarctica, in 2007. Many PSCs were observed between July and August 2007. We succeeded in identifying the features of Ice (Type-II), NAD and or β-NAT (Type-Ia), and STS (Type-Ib) PSCs in the zenith sky infrared spectra measured by FTIR. departmental bulletin paper